THE IMPACT OF GLOBALIZATION ON EDUCATIONAL CHANGE - Suranto, Dwi Iwan; Annur, Saipul; Ibrahim, Duski (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2023)
Globalization is a process of losing boundaries between world communities. In the current era of globalization, there are many cultures that enter and develop in Indonesia. Both culture that has a good or bad impact on the lives of Indonesian people. The existence of reporting must be accompanied by a wise attitude so that it can be utilized properly and can become knowledge that has a positive impact on us. Globalization concerns various aspects of life, one of which is education. Because it involves various aspects, globalization greatly affects and changes the order of human life. The purpose of this writer is to determine the impact of globalization on changes in education. The method used in this research is library research or literature study. By searching for various written materials from books, articles, and relevant journals. The results of this study are that globalization is a process of expanding foreign culture into local culture, where there is dependence between countries around the world. Thus giving birth to a global society, which influences human life including education. The results of the growth of globalization have had positive and negative impacts on education. The positive impact is the ease of accessing educational information, increasing the quality of educators, increasing the quality of education. As for the negative impact, the decline in the moral quality of students, the erosion of local culture, and the emergence of fast and instant traditions.